Vanadium[ethyl tricyanoethylene carboxylate]x: a new organic-based magnet1. Issue 28 (28th July 2015) - Lu, Yu; Yu, Howard; Harberts, Megan; Epstein, Arthur J.; Johnston-Halperin, Ezekiel
<x xml:space="preserve">Abstract</x> A new organic-based magnet with Tc of 145 K is prepared and characterized and benchmarked against its analogues.